Interactions of allopathic drugs with Ginkgo biloba and Valeriana officinalis herbal medicines (Research, Society and Development, 2021)
Herbal medicine is a science that studies the action of plants in therapeutic use and the drugs produced from this study are called herbal medicines. Drug interactions (IM) can affect the efficacy and safety of treatment with herbal medicines, therefore, their use must occur correctly, effectively and safely. The objective was to identify potential drug interactions between drugs and herbal medicines based on Ginkgo biloba (GB) and Valeriana officinalis (VO), as well as the potential adverse events of these interactions. The proposed study is based on an analysis of the use of some herbal medicines with allopathic medicines, being a search in the Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Latin American and Caribbean Health Sciences (LILACS) databases and Scientific Electronic Library Online (SciELO), Academic Google, with the proposed time period from 2010 to 2020, using as descriptors: Drug Interaction Ginkgo biloba, Drug Interaction Valeriana officinalis. Including interactions that appear in the IBM Micromedex® interactions program and excluding interactions of light severity and/or that are not included in the program. IM potentials of GB were identified with anti-inflammatory and anticoagulant drugs, increasing the risk of bleeding, and UM potential of VO with drugs and depression of the central nervous system. The use of these herbal medicines needs monitoring, especially when the patient is already using polypharmacy.